A RARE BYZANTINE LEAD SEAL FROM MEDIEVAL BUČIN (Annual of the Faculty of Philosophy in Skopje, 2021)
For centuries the Byzantines, from humble monks and laymen to highly placed grandees and emperors, used lead seals to “lock” official and private correspondence and to validate or authenticate documents. The details contained on seals preserved shed light on many aspects of the Byzantine world, principally the structure of its civil, military, and ecclesiastical administrations, the careers and locations of its officials, and the responses to the ever-changing fortunes of the empire over its millennial existence. The inscriptions on the seals echo, as their images reflect, the beliefs and perspectives of people who but for the survival of their seals would be lost to history. The seals often provide the key evidence needed to outline a career, to chart the rise and decline of a family, or to confirm the presence of an individual at a given place or time. One such rare specimen, found during archaeological field surveys within the project “Old Towns and Fortifications 2019” in the vicinity of the site Kale, medieval Bučin, gives us information about its owner, a member of the highest Byzantine aristocracy, and illfated emperor from turbulent times of late 12th – early 13th century.